Taromancia, o que sabemos: um estudo exploratório sobre a taromancia hodierna no Brasil - Rosendo, Patrícia Andrade (2021)
Through participatory observation from an insider perspective, the elements that make up the popular imagination were recognized, and the presence of a Taromancy stereotype can be observed, namely, that it is supposedly an esoteric-mediumistic practice, that is, a practice that presupposes a direct relationship between the practitioner, but also the cards, with the beyond. Data were collected between January 3rd and February 1st, 2021, through objective questionnaires aimed at both the general public and professionals, seeking to explore the popular imagination and current practice to diagnose whether and what changes took place at the beginning of the current century. From the author's insider point of view, we hypothesize that, despite the resistance of the stereotype that remains from the colonial era, a secularization of the profession is taking place. Based on the recognition of the stereotype, we resorted to bibliographical research to investigate the historical course of its formation from the origin of the cards, from their arrival in colonial Brazil in the nineteenth century to the present day, revealing a historical trajectory that not for nothing has sedimented such stereotype in the Brazilian imagination. This study corroborates the hypothesis and affirms the process of secularization of Taromancy that began at the end of the 20th century and solidified at the beginning of the 21st century. Thus, with this research, we sought to contribute to academic research on the phenomenon through the production of knowledge to assist in the social repositioning of 21st-century Taromancy.